A comparison of coherency measurement using semblance and multiple signal classification, from a seismic-while-drilling perspective - Sun, B.; Bona, Andrej; King, A.; Zhou, B. (Society of Exploration Geophysics, 2014)
© 2015 Society of Exploration Geophysicists.A diamond drill bit is usually considered to be an inadequate seismic vibration source. To detect and use weak drillbit-generated seismic wavefields in hard-rock drilling, we compared different coherency measures between a conventional method of semblance and a generalized multiple signal classification (MUSIC) algorithm. We tested the detectability and resolution differences between semblance and MUSIC with synthetic examples. MUSIC coherency has the advantage of higher resolution over semblance measurement when the source wavefronts are accurately predicted. In addition, we applied both methods to detect the coherent moveout of a diamond drill-bit signal from a hard rock seismic-whiledrilling experiment at Hillside, South Australia. We used the coherent moveout to estimate the overburden velocity around the borehole. We also performed interferometry migration using the coherency measurements to image the drillit position. Our analysis determined that the direct waves generated from a diamond drill bit at shallow depths can be successfully detected, allowing drill-bit imaging and the determination of formation velocity around the borehole.